The efficacy and mechanisms of low-intensity transcranial ultrasound stimulation on pain: a systematic review of human and animal studies - Hao-Ran Xu; Yiu-Liang Yi; Chuan Xue; Zi-Qi Guo; Li Ding; Jie Jia (The Journal of Headache and Pain)
Abstract Background Low-intensity transcranial ultrasound stimulation (LITUS) is an emerging non-invasive neuromodulation technique for pain treatment, with the unique ability to modulate deep brain nuclei associated with pain. The aim of this study is to systematically review and summarize the evidence for the efficacy of LITUS in pain management and to elucidate the potential mechanisms underlying its analgesic effects. Methods A systematic search was conducted across five databases up to Mar 31st, 2025. Controlled studies in both human and animal subjects were included. Two independent reviewers completed the screening and risk of bias assessment process following predefined inclusion and exclusion criteria. Results A total of thirteen studies were included in the review. These studies demonstrated LITUS’s potential in managing various types of pain among different populations and animal models, particularly targeting the anterior cingulate cortex, thalamus, insular cortex, primary sensorimotor cortex, and periaqueductal gray. Most included studies showed positive effects and verified the safety of LITUS on pain, reporting few adverse effects. Conclusions LITUS is an effective and non-invasive tool for pain regulation in animals and humans, enabling precise modulation of deep brain circuits. Analgesic effects may be affected by pain-related risk factors, insufficient dosage, suboptimal protocols, and target selection. Initial evidence has highlighted the direct link between LITUS parameters, brain region responses, and pain behavior. Modulation of brain excitatory, nociceptive circuit, electrophysiological response, autonomic response, biochemistry, neuroinflammation, and psychology are proposed as the potential mechanisms underlying the efficacy of LITUS. More high-quality research is urgently needed to advance clinical LITUS use and reveal its mechanisms.